The Scourge of Aflatoxins in Kenya: A 60-Year Review (1960 to 2020) - Omara, Timothy; Kiprop, Ambrose K; Wangila, Phanice; Wacoo, Alex Paul; Kagoya, Sarah; Nteziyaremye, Papias; Odero, Mark Peter; Nakiguli, Caroline Kiwanuka; Obakiro, Samuel Baker (Journal of Food Quality, 2021)
Aﬂatoxins are endemic in Kenya. The 2004 outbreak of acute aﬂatoxicos is in the country was one of the unprecedented epidemics of human aﬂatoxin poisoning recorded in mycotoxin history. In this study, an elaborate review was performed to synthesize Kenya’s major ﬁndings in relation to aﬂatoxins, their prevalence, detection, quantiﬁcation, exposure assessment, prevention, and management in various matrices. Data retrieved indicate that the toxins are primarily biosynthesized by Aspergillus ﬂavus and A. parasiticus, with the eastern part of the country reportedly more aﬂatoxin-prone. Aﬂatoxins have been reported in maize and maize products (Busaa, chan’gaa, githeri, irio, muthokoi, uji, and ugali), peanuts and its products, rice, cassava, sorghum, millet, yams, beers, dried ﬁsh, animal feeds, dairy and herbal products, and sometimes in tandem with other mycotoxins. The highest total aﬂatoxin concentration of 58,000 μg/kg has been reported in maize. At least 500 acute human illnesses and 200 deaths due to aﬂatoxins have been reported. The causes and prevalence of aﬂatoxins have been grossly as cribbed to poor agronomic practices, low education levels, and in adequate statutory regulation and sensitization. Low diet diversity has aggravated exposure to aﬂatoxins in Kenya because maize as a dietetic staple is aﬂatoxin-prone. Detection and surveillance are only barely adequate, though some exposure assessments have been conducted. There is a need to widen diet diversity as a measure of reducing exposure due to consumption of aﬂatoxin-contaminated foods.
Keywords: Aﬂatoxins; Kenya; 60 years; Outbreak